Focus on Adoption: Changes, Evolution and Areas of Tension - Chateauneuf, Doris; Piché, Anne-Marie; Lavallée, Carmen (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2024)
Research framework: Adoption has existed for many years as an institution that promotes family ties, taking forms that vary based on place, culture and time . However, the ways in which the social actors involved use adoption reveal specific conceptions of the child, the family, affiliations and family relationships. Objectives: This issue aims to identify the evolution of certain social and legislative adoption practices and to discuss the family and identity realities associated with adoption, in order to provide an analysis of how it has changed over time. Methodology: The articles in this issue highlight the many aspects of adoption: not only does it affect a number of different actors (adopters, adoptees and parents of origin), but it also raises concerns and questions of a social, legal and family nature. Results: Adoption is a subject of study at the intersection of several disciplines, including law, anthropology, sociology, psychology and social work. The various cases discussed in this issue also illustrate the importance of reflecting on the implications of adoption for individuals, families and society as a whole. Conclusions: The cases cited in these articles illustrate the need to approach adoption from a dynamic perspective that takes into account the evolution, contexts and changes involved in all the issues associated with it. Contribution: This issue is intended to stimulate reflection, both now and in the future.